Intelligent computer graphics 2009 - Plemenos, Dimitri. (Springer London :, 2009)
The purpose of this volume is to present current work of the Intelligent Computer Graphics community, a community growing up year after year. This volume is a kind of continuation of the previously published Springer volume "Artificial Intelligence Techniques for Computer Graphics". Nowadays, intelligent techniques are more and more used in Computer Graphics in order, not only to optimise the processing time, but also to find more accurate solutions for a lot of Computer Graphics problems, than with traditional methods. This volume contains both invited and selected extended papers from the last 3IA Conference (3IA 2009), which has been held in Athens (Greece) in May 2009. The Computer Graphics areas approached in this volume are behavioural modelling, declarative modelling, intelligent modelling and rendering, data visualisation, scene understanding, realistic rendering, and more. Realistic Skin Rendering on GPU -- Affective States in Behavior Networks -- Information Theory Tools for Viewpoint Selection, Mesh Saliency and Geometry Simplification -- Classifying Volume Datasets Based on Intensities and Geometric Features -- Light Source Storage and Interpolation for Global Illumination: A Neural Solution -- An Intelligent System for Overlaying Texts on Background Images Based on Computational Aesthetics -- Parallel Coordinates: Intelligent Multidimensional Visualization -- An Adjectival Interface for Procedural Content Generation -- An SVM/GA Hybrid Framework for Qualitative Knowledge Aided 3D Scene Synthesis -- Machine Learning and Pattern Analysis Methods for Profiling in a Declarative Collaorative Framework -- AURAL: An Evolutionary Interface for a Robotic Sonification Process.